Perancangan Sistem Kontrol Tungku Heat Treatment Elektrik Berbasis Mikrokontroler - Putra, Meiki Eru; Pratama, Aditya (LPPM Universitas Dharma Andalas, 2023)
Low carbon steels are materials that are mostly used as materials of general construction. Because low carbon steels have high ductility, but the hardness is low and not wear resistant. This can be solved by changing the properties of the available material by the heat treatment process. The microstructure depends on the process experienced, especially the heat-processing process received during the process. Heat resistance to low carbon steel is important. Heat Treatment is one of the processes to change the metal structure by heating the specimen on electric trance (furnace) at recrystallization temperature for a certain period of time then cooled to cooling medium such as air, water, oil and diesel which each have different density cooling. In this heat treatment process the heating temperature is 800-900oC, 60% carbon powder and 40% Barium Carbonate as energizer which accelerates the process, the holding time is 20 minutes with the cooling medium is SAE 20 - 50 oil. The result is a material structural change that undergoes heat treatment process with the longest detention time of 20 minutes with a temperature of 900oC.From the results of material testing data it can be obtained a conclusion that the heat treatment obtained material that has high hardness on the surface and still soft on the inside.